Role of Sustainable Alternatives to Petrochemical Based Plastics in Achieving the SDGS - Sajid, Syeda Azka; Tehseen, Palwasha; Mahmood, Umair; Ghaffar, Aisha; Qasim, Muhammad; Arooj, Rimsha; Tahir, Tehreem; Rafique, Zunaira (Indonesian Journal of Agriculture and Environmental Analytics, 2024)
A significant transition from fossil fuel-based economy to one based on biomass is occurring as a result of global warming, socioeconomic challenges, and new policies, which are propelling decarbonisation process across industries. The usage of bioplastics is the most effective way to address the issue of plastic trash. Bioplastics are a safe and sustainable substitute for petrochemical or traditional plastics that lessen our reliance on fossil fuels. The strategic substitution of sustainable products for those derived from petrochemicals not only promotes environmental conservation but also advances the achievement of several sustainable development goals (SDGs). Post-treatment methods, such as photolysis, thermochemical treatment, and biodegradation were used in this study. These alternatives support in lowering greenhouse gas emissions and increasing resource efficiency, which greatly supports SDGs 12 and 15, Responsible Consumption and Production and Life on Land, respectively. This study explores how the (SDGs) could be implemented effectively and makes it clear that sustainable consumption and production (SCP) should be given significant consideration in their production.